Climate Disaster Preparedness - Dennis Del Favero; Susanne Thurow; Michael J. Ostwald; Ursula Frohne (Springer Nature Switzerland, 2024)
As a result of global warming, extreme events, such as firestorms and flash floods, pose increasingly unpredictable and uncertain existential threats, taking lives, destroying communities, and wreaking havoc on habitats. Current aesthetic, technological and scientific frameworks struggle to imagine, visualise and rehearse human interactions with these events, hampering the development of proactive foresight, readiness and response.This open access book demonstrates how the latest advances in creative arts, intelligent systems and climate science can be integrated and leveraged to transform the visualisation of extreme event scenarios. It reframes current practice from passive perception of pre-scripted illustrations to active immersion in evolving life-like interactive scenarios that are geo-located. Drawing on the multidisciplinary expertise of leaders in the creative arts, climate sciences, environmental engineering, and intelligent systems, this book examines the waysin which climate disaster preparedness can be reformulated through practices that address dynamic and unforeseen interactions between climate and human life worlds. Grouped into four sections (picturing, narrating, rehearsing, and communicating), this book maps this approach by exploring the emerging strengths and current limitations of each discipline in addressing the challenge of envisioning the unpredictable interaction of extreme events with human populations and environments. This book provides a timely intervention into the global discourse on how art, culture and technology can address climate disaster resilience. It appeals to readers from multiple fields, offering academic, industry and community audiences novel insights into a profound gap in the current knowledge, policy and action landscape.